Arabic Printing for the Christians in Ottoman Lands The East-European Connection - Feodorov, Ioana (Early Arabic Printing in the East, 2023)
In Eastern Europe and the Ottoman Levant, Arabic printing began with the work of Antim the Iberian, a scholar and metropolitan of Wallachia, and Athanasios III Dabbās, patriarch of the Church of Antioch and metropolitan of Aleppo. The book presents the first Arabic press in the Ottoman lands, founded in 1705 in Aleppo due to a transfer of Romanian printing tools and expertise, and the later presses of Lebanon that produced Christian Arabic books.